Building and Sustaining National ICT/Education Agencies : Lessons from the Philippines - Vergel de Dios, Benjamin (World Bank, Washington, DC, 2017)
Beginning in 1996, the Department of Education (DepEd) started to implement the first large scale ICT/education initiative in the Philippines. This effort was later strengthened and expanded to become the DepEd Computerization Program and DepEd Internet Connectivity Program (DCP/DICP). This was a huge undertaking for DepEd, both to oversee and to implement. Fortunately, many groups were willing to help – other government agencies, international and non-government organizations, private sector, local government units and higher education institutions. That said, coordinating the large scale implementation of ICT/education initiatives, as well as related donations and support from partners and key stakeholder groups, made it difficult to share information and expertise, coordinate public-private partnerships, and replicate and scale up successful projects. Many countries have created a distinct agency to coordinate and implement ICT/education. In the early stages of the introduction of ICTs in education in the Philippines, the government largely resisted this idea, although a number of related oversight and implementation models were proposed. Absent such an organization and/or related formal institutional structure education policymakers, stakeholders and practitioner groups explored other options.